Developing, Modelling and Assessing Second Languages - Keßler, Jörg-U; Lenzing, Anke; Liebner, Mathias (John Benjamins Publishing Company, 2016)
This edited volume brings together the work of a number of researchers working in the framework of Processability Theory (PT), a psycholinguistic theory of second language acquisition (SLA) (Pienemann 1998; 2005). The aim of the volume is two-fold: It engages with current issues in both theory development and theory application and focuses on theoretical developments within the framework of PT as well as issues related to second language teaching and assessment. In coordinating approaches to addressing both theoretical and applied aspects of SLA, this volume aims at bridging the gap between theory and practice. It also reflects the richness of debate within the field of PT-based research. The volume is intended for postgraduate students, SLA researchers as well as language teachers.